Vpliv različnih načinov razžagovanja na ekonomsko učinkovitost - Gornik Bučar, Dominika (Les (Ljubljana), 2010)
The production aim is to produce products of certain value at the lowest cost.Raw materials and available technologies have large impacts on the production costs. The most common sawing methods of coniferous logs are live and cant sawing. In the present study we compared both sawing methods. Quantity and quality yield and the average variable costs of sawing were compared. To determine which sawing method achieves a higher contribution margin ratio of fixed costs and profits "direct costing method" was used. The results showed that small diameter logs are not suitable for production of desired products, regardless of the chosen sawing methods. By larger diameter logs sawing we achieved bigger economic efficiency by cant sawing.
Keywords: lesnopredelovalna industrija; iglavci; razžagovanje hlodovine; izkoristek; stroški